2017
DOI: 10.1186/s10397-017-1006-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal McCall culdoplasty versus laparoscopic uterosacral plication to prophylactically address vaginal vault prolapse

Abstract: BackgroundStudies have shown that vaginal vault prolapse can affect up to 43% of women following hysterectomy for pelvic organ prolapse. Many techniques have been described to prevent and treat vaginal vault prolapse. The primary objective of our study was to compare McCall’s culdoplasty (when performed along side vaginal hysterectomy) with laparoscopic uterosacral plication (when performed along side total laparoscopic hysterectomy) for prevention of vaginal vault prolapse. Secondary outcomes included inpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Based on a large community based retrospective cohort study, factors that increase the risk of POP are older age, postmenopausal status, parity, elevated intraabdominal pressure and overweight [ [10] , [11] , [12] ]. Additionally, it seems that a combination of support defects in the anterior, posterior, and apical vaginal segments, abnormalities of connective tissue structure or its repair mechanism might predispose women to the development of POP [ 10 , 11 , 13 ]. It is well accepted that the USL plays an important role in the pelvic support system, with quantity, structure and organization of the extracellular matrix (ECM) being key elements of the tissue’s stability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a large community based retrospective cohort study, factors that increase the risk of POP are older age, postmenopausal status, parity, elevated intraabdominal pressure and overweight [ [10] , [11] , [12] ]. Additionally, it seems that a combination of support defects in the anterior, posterior, and apical vaginal segments, abnormalities of connective tissue structure or its repair mechanism might predispose women to the development of POP [ 10 , 11 , 13 ]. It is well accepted that the USL plays an important role in the pelvic support system, with quantity, structure and organization of the extracellular matrix (ECM) being key elements of the tissue’s stability [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Shull procedure is proven better in terms of sexual function. Along with Schiavi et al 7 , the study by Niblock et al 8 also showed a low percentage in vaginal vault prolapse occurrence following McCall culdoplasty procedure (0%). Otherwise, in USP procedure, vaginal vault prolapse occurrence rate following hysterectomy were higher (16.4%).…”
Section: Resultsmentioning
confidence: 78%
“…In contrast to Schiavi et al 7 , the study performed Niblock et al 8 had a shorter follow-up period, with a mean of follow-up was 36 months for McCall culdoplasty group and 41 months for laparoscopic USP group; whilst the shortest follow-up period is 5 months. The relatively short follow-up periods could be a source of bias due to the possible occurrence of vaginal vault prolapse in this period was still low.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…They were found to be comparable in terms of the complications encountered. Laparoscopic uterosacral plication has a statistically significant shorter hospital admission, but MC has proven to be superior to laparoscopic uterosacral plication in terms of patients presenting with subsequent pelvic organ prolapse [24]. Another study reported that laparoscopic uterosacral ligament colpopexy appears to achieve a good anatomical outcome and is safer and more reliable than the transvaginal approach [25].…”
Section: Discussionmentioning
confidence: 99%